2018
DOI: 10.1111/jocn.14378
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and informational needs on sexual health in people with epilepsy or multiple sclerosis: A focus group investigation

Abstract: Implementation of improved patient information at the neurological clinic is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Overall, the present study shows that patients with MS and epilepsy report a high prevalence of sexual dysfunction. The results support the findings from a previous focus group investigation reporting that patients seldom highlight sexual problems when talking to health professionals, which may result in sexual distress and impact both psychological wellbeing and the relationship with a partner [31]. Some sexual problems may be related to the current disease, whereas other sexual problems may be triggered by more psychological and social aspects.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Overall, the present study shows that patients with MS and epilepsy report a high prevalence of sexual dysfunction. The results support the findings from a previous focus group investigation reporting that patients seldom highlight sexual problems when talking to health professionals, which may result in sexual distress and impact both psychological wellbeing and the relationship with a partner [31]. Some sexual problems may be related to the current disease, whereas other sexual problems may be triggered by more psychological and social aspects.…”
Section: Discussionsupporting
confidence: 88%
“…Other factors may complicate the sexual lives of patients with epilepsy. In a qualitative study including 26 patients, Egerod et al found that patients with epilepsy feared an epileptic seizure if they let go during sexual activity and, therefore, do not achieve satisfaction and/or orgasm by intimate contact [31] . This was supported by Rees et al in describing sexual auras and erotic feeling as part of seizures [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations